Vygotsky in present days (Fractal: Journal of Psychology, 2015)
In this paper, we discuss the topicality of the cultural-historical theory developed by Lev Semionovitch Vygotsky approximatelybetween the end of the second decade and the third decade of the 20th century. We adopt a critical attitude towards theidea that scientific knowledge has an expiration date, and we seek to show that this idea emerges from the transformationof science into a commodity. As a counterpoint to this view, we argue that every device built by man presents somethingpermanent which transcends the mere functionality of things produced for consumption. In other words, we argue that allthat is singular, in a way, has permanence in the world.